2018
DOI: 10.1177/0887302x18783580
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Rock Climbers’ Functional Needs in Climbing Pants

Abstract: Researchers assessed climbers' pants by investigating whether a pants' style or brand preference exists among rock climbers, along with looking at fit, mobility, comfort, protection, and donning/ doffing expectations for climbing pants using a mixed-methods design study. Active adult rock climbers, aged 19 or older, were conveniently sampled at two U.S. rock-climbing events and completed a questionnaire. The researchers found that rock climbers needed improvements in their pants' fit, sizing options, and desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…In addition, empirical studies have indicated that functional performance and aesthetic appearance, rather than expressive consideration, are essential factors for sportswear (Dickson and Pollack 2000). Furthermore, to fit individual study contents, many empirical studies have also excluded expressive considerations (e.g., Jin and Black 2012;Michaelson 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, empirical studies have indicated that functional performance and aesthetic appearance, rather than expressive consideration, are essential factors for sportswear (Dickson and Pollack 2000). Furthermore, to fit individual study contents, many empirical studies have also excluded expressive considerations (e.g., Jin and Black 2012;Michaelson 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Poor fitting clothing further restrains movement (Michaelson 2015). For example, loose thigh or tight crotch of rock climbing pants influenced climbers' movement (Michaelson 2015), garments with excess bulk inhibit sailors' mobility (Bye and Hakala 2005), and tight sleeves restrict tennis players when serving tennis balls (Jin and Black 2012). Similarly, ill-fitting martial arts pants (e.g., too narrow or too big) may restrict high kick actions.…”
Section: Current Uniform Attributes and Expected Performance Of New Umentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was developed based on the published functional apparel studies and the FEA model. 30,[39][40][41][42][43] The FEA model was developed by Lamb and Kallal (1992) to assess functional, expressive and aesthetic considerations to identify the consumer needs. 44 The FEA model has been widely used in functional garment studies such as sailing apparel, tennis wear, climbers' pants and clothing needs of adolescent girls with disabilities.…”
Section: Evaluation and Wear Trialmentioning
confidence: 99%
“…For design of functional clothing, similar research methods and procedures have been applied to develop an understanding of customers' needs in various other activewear categories, some of which include design development for sailing clothing [24], female collegiate basketball players [25], female collegiate golf teams [26], inline skaters [5], dance practicewear [27] and rock climbers [28].…”
Section: Similar Projects Employing Cross-national Comparisons Inmentioning
confidence: 99%